The Effect of Oxygen Plasma Treatment on Wrinkle Resistance of Cellulose Acetate Based Fabric - Seyda Eyupoglu; Cengiz Karabulut; Serdar Erdem Gül; Ahmet Tamer Esener; Fırat Yılmaz; Mazyar Ahrari; Can Eyupoglu; Dilek Kut (Journal of Natural Fibers, 2022)
In this study, cellulose acetate-based fabrics were subjected to a resin-based wrinkle-resistant treatment. The fabric samples were treated with oxygen plasma for 1 and 5 minutes with a power of 100W prior the wrinkle-resistance finishing to enhance wrinkle resistance. The surface morphology and functional groups of samples were analyzed with scanning electron microscopy and Fourier transform infrared spectroscopy, respectively. The angle of wrinkle-resistance and tensile strength of samples were investigated in accordance with resin type and plasma treatment. Scanning electron microscope micrographs reveal that plasma treatment generates microscopic grooves and micro-cracks on the sample surfaces, resulting in an etching effect. Furthermore, the samples have been successfully treated with resin-based wrinkle-resistant finishing. The results of Fourier transform infrared spectroscopy show that no significant alterations in functional groups formed in the acetate fibers posterior to plasma treatment. The wrinkle-resistance angle of cellulose acetate cloth pre-treated with oxygen plasma and wrinkle-resistance resin was significantly improved, according to the results. The high wrinkle resistance result was obtained for warp direction 113.5 ± 3.5 and weft direction 102 ± 3. Furthermore, the wrinkle resistance data were investigated using MATLAB R2020b to predict one-way ANOVA with the main factor, plasma treatment, and the interaction impact was extremely significant (P < .05). The ANOVA results resemble that plasma treatment has an influence on sample wrinkle resistance. Furthermore, with plasma treatment, sample tensile strength increases from 525.15 N to 530.76 N, but with wrinkle-resistance resin, it decreases. Consequently, plasma pre-treatment and wrinkle-resistance resin are anticipated to suit both the needs of eco-friendly and high-quality finishing methods for textile materials.